KUR'AN'DA GEÇEN LUGAVÎ İDGAM'IN VE FEKK-İ İDGAM'IN SES DELALETİNE ETKİSİ [1-13] - Ekhtıar, Ousama (Fırat University, 2017)
Bu çalışma, Kur'anı Kerim’deki lügavi idgamı, geçtiği ayetlerin siyak ve sibakı üzerinde meydana getirdiği etkileri açısından ele almaktadır. Ayetlerin peşpeşe ve düzenli olarak gelmesi ses açısından önem taşıdığı bilinmektedir. İşte bu çalışma ilk kez idgamın geçtiği ayetlerde, idgamın yapılması durumunda ortaya çıkan “Hafa” delaleti, idgamın yapılmaması durumunda ise ortaya çıkan “mücahere” delaleti başta olmak üzere idgamın çeşitli delaletlerini işleyecektir. Aynı zamanda, ayette tek başına geçen idgam, tek başına geçen fekk-i idgam, bir arada geçen hem idgam hem fekk-i idgam gibi Kur'an'da idgamın geçtiği çeşitli şekillerini işleyeceğiz. Çalışmamızda lugâvî idgamın Kur’an’daki ses olgusunun oluşmasını sağlayan delaletlerini incelemeye çalışırken, şekilsel olarak Lugâvî idgamı ele almayacağız. Zira bu husus, okuyuşla alakalı bir durumdur ve bu konuyu ele alan birçok çalışma bulunmaktadır. Bu nedenle idgamın, çağdaş çalışmaların değinmediği yeni bir yönünü işleyeceğiz. Söz ettiğimiz bu yeni yön de mudgam ve muzharın sesinden anlaşılan delalet konusudur. İdgamın ifade ettiği delaletleri, ayetlerin sebeb-i nüzulundan ya da siyak ve sibakından yola çıkarak ve semantik metoda başvurarak temellendirmeye çalışacağız. Son olarak çalışmamızın sonunda, konuyla ilgili vardığımız önemli bulgulara yer vereceğiz

This article examines the subject of linguistic merging in the Qur'an in terms of its effect in the formation of significance in the context of the verse and the verses before it in the Holy Quran. It is known that the sound has got a significance in the context of relay and regularity. But what is new in this article is that it studies significance of concealment in case of merging and significance of manifestation in case of unscrew merging. It also studies the forms of the recitation of merging and unscrew in the verses of the Holy Quran, in the terms of recitation of linguistic merging alone, or recitation of unscrew alone, or recitation of the both of them in the context of the same verse. It studies the significances of the two the same merging. We will try to influence the meanings of linguistic merging's significances to build a perception of that acoustic phenomenon in the Holy Quran. We do not care about the acoustic phenomenon in terms of formality. This is a clear rhythmic issue that has been mentioned by many researches. So, we are going to discuss a new aspect that has not been used in recent researches. It is the subject of the significance learned from the sound of merging or clarity. We will link the analysis of the significance of merging with the appropriate evidences that taken from the science of circumstances of revelation to link the subject of the significance of the merging in the verses with their circumstances of revelation, or with their the general semantic context. In the study of this issue we will follow the method of semantic analysis of the meaning of sound in its context in terms of clarity and concealment. At the end of the research we conclude with the most important results which relate to our observations on this subject